Evaluation of Financial Determinants of Biological Assets of Agricultural Companies in Nigeria - Nnajieze, Elizabeth Ifeyinwa (International Journal of Accounting and Financial Reporting, 2022)
This study examined the financial determinants of biological assets of agricultural companies in Nigeria. The specific objectives were to examine the effect of leverage, profitability, and firms size on the biological assets of quoted Agricultural firms in Nigeria. The study adopted ex-post facto research design and made use of secondary data collected from annual reports and accounts of the sampled agricultural firms for a period of ten (10) years (2011-2020). Ordinary Least Squares (fixed effect model) were applied to evaluate the determinants (leverage, profitability, & firm size) of biological assets of quoted agricultural firms in Nigeria. The result of the analysis showed that leverage has a significant effect on the biological assets of quoted agricultural firms in Nigeria. The other variables which include profitability measured by return on assets and firm size have an insignificant effect on biological assets. The implication is that only leverage can cause a significant increase or decrease in the biological assets of agricultural firms in Nigeria. The study conclude that leverage is the only financial determinant that have significant effect on biological assets of agricultural firms in Nigeria.